Morphometric Analysis of Sphenopalatine Foramen on Computed Tomography Imaging for localization of Sphenopalatine Artery - Zandi, Afsoon; Safavi Naini, Ali; Ghorbani, Jahangir; Raad, Nasim; Karimi-Galougahi, Mahboobeh (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2023)
Background: Epistaxis affects about 10% of those seeking medical treatment, with posterior epistaxis from the sphenopalatine artery (SPA) posing management challenges. The sphenopalatine foramen (SPF) is crucial for interventions, and CT imaging aids preoperative planning by detailing the SPF and adjacent structures. Aim: Performing a morphometric analysis of the sphenopalatine foramen using CT imaging to identify and quantify anatomical landmarks that help surgeons locate the sphenopalatine artery. Methods: A retrospective observational study analyzed Sinus CT scans from 200 adult patients to measure the sphenopalatine foramen’s anteroposterior and craniocaudal dimensions. Distances from the SPF to key anatomical landmarks, such as the maxillary line and anterior head of the middle turbinate, were also measured. Statistical analysis was performed to assess variations based on sex and side of the nasal cavity, with a significance level set at p < 0.05. Results: The average size of the SPF was 5.01 mm ± 1.37 in the anteroposterior dimension and 5.58 mm ± 1.71 in the craniocaudal dimension. The mean distances to anatomical landmarks were as follows: maxillary line 35.73 mm ± 2.47, anterior head of the middle turbinate 33.76 mm ± 4.52, basal lamella 9.71 mm ± 1.84, choanal arch 8.78 mm ± 1.62, posterior fontanelle of the maxillary sinus ostium 14.49 mm ± 1.32, and the bony attachment of the inferior turbinate 13.89 mm ± 2.01. The height above the nasal floor was 25.69 mm ± 2.43. Males exhibited longer distances to key landmarks compared to females, with no significant differences noted between the right and left nasal cavity sides. Conclusion: Preoperative CT imaging effectively identifies key bony landmarks for accurately locating the sphenopalatine foramen, enhancing the safety and efficiency of endoscopic approaches to the sphenopalatine artery, especially in managing posterior epistaxis.